Model and control of the DC–DC modular multilevel converter with DC fault tolerance. Issue 4 (1st October 2020) - Gruson, François; Tlemcani, Amine; Li, Yafang; Delarue, Philippe; Le Moigne, Philippe; Guillaud, Xavier
ABSTRACT: This paper presents the modelling of the DC–DC multilevel modular converter (DC–DC MMC) with half-bridge sub-modules and the control based on the inversion of its model. The DC–DC MMC presents many advantages such as its modularity, the absence of capacitors on the DC-bus voltage and a low switching frequency. This topology also preserves the intrinsic disadvantages of the MMC as the complexity controlling due to the large number of semiconductors and state variables to control. The control of this converter cannot be symmetrical due to the interconnection of the two parts by an internal AC grid. The control strategy of one part of the DC–DC MMC uses the conventional control scheme with current controls and stored energy control. The second one uses the energy control and produces the waveform of the three-phase internal AC bus voltage linking the two parts of the converter. The explicit control for the generation of internal AC voltages guarantees the correct operation of the converter even in a critical DC-voltage dip on DC buses. Thus, it avoids the need of a DC circuit breaker or the use of full-bridge MMC sub-modules. The validity of the proposed control is verified by simulation.